Corneal Rigid Gas Permeable Contact Lens in Corneal Scarring: a Case Report: Poster Presentation - Case Report - Resident - Regina Ivanovna; Umar Mardianto (Majalah Oftalmologi Indonesia, 2023)
Introduction : Corneal scarring is part of corneal wound healing response to injury, surgery, or infection to the cornea. Corneal scarring causes significant visual reduction. This case report highlights visual acuity (VA) improvement in patient with corneal scarring following rigid glass permeable contact lens (RGP-CL) Case Illustration : A 25 year-old male presented blurry vision in right eye (RE) due to trauma. His VA was 3/60 on RE and 6/6 on left eye (LE). The best corrected visual acuity (BCVA) of RE was 6/45 (S-1.25 C-5.00 X 180°). Slit lamp examination of RE showed corneal scarring in central area and deep neovascularization. Keratometry readings obtained 39.50D (8.48mm) at 170 degree and vertical curvature of 44.00D (7.68mm) at 80 degree, with markedly irregular mires of RE. A trial fitting was performed for RE by using tisilfocon A lens with base curve of 8.30 mm, power S-4.00D and diameter 9.20 mm. The over-refraction with trial lens obtained a total refractive error of S-6.00 with cylindrical correction neutralize with RGP. The achieved BCVA by over-refraction was 6/45 with comfortable fit. Discussion : Rigid permeable lens (RGP) is an option in dealing with irregular astigmatism due to corneal scarring. The RGP fitting works best especially when the corneal scarring is not in the center of visual pathway. Rigid lens works by providing tear-lens power and creating smooth surface to neutralize the irregular cornea. Good RGP-CL fitting could help patient with corneal carring gain better VA. Conclusion : Good rigid permeable contact lens fitting could help patients with corneal scarring gain better VA.